2016
DOI: 10.1128/aem.03660-15
|View full text |Cite
|
Sign up to set email alerts
|

Loop-Mediated Isothermal Amplification (LAMP) for Rapid Detection and Quantification of Dehalococcoides Biomarker Genes in Commercial Reductive Dechlorinating Cultures KB-1 and SDC-9

Abstract: c Real-time quantitative PCR (qPCR) protocols specific to the reductive dehalogenase (RDase) genes vcrA, bvcA, and tceA are commonly used to quantify Dehalococcoides spp. in groundwater from chlorinated solvent-contaminated sites. In this study, loopmediated isothermal amplification (LAMP) was developed as an alternative approach for the quantification of these genes. LAMP does not require a real-time thermal cycler (i.e., amplification is isothermal), allowing the method to be performed using less-expensive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…Direct amplification, i.e., amplification without DNA extraction or purification, satisfies both these attributes. Elimination of DNA extraction and purification steps simplifies the process and may avoid the need for sample transport [ 3 , 4 ]. For detection of invasive species at very low abundance, sample concentration is often useful and necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Direct amplification, i.e., amplification without DNA extraction or purification, satisfies both these attributes. Elimination of DNA extraction and purification steps simplifies the process and may avoid the need for sample transport [ 3 , 4 ]. For detection of invasive species at very low abundance, sample concentration is often useful and necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The chip configuration consisted of eight reaction wells per sample lane, and four sample lanes per chip (i.e. 32 reaction wells per chip, each with 20 μL reaction volume), as previously described (Kanitkar et al, 2016). Primers targeting rdhA gene and 16S rRNA gene were each dispensed into three separate reaction wells per sample lane, and primers targeting the MIAC were dispensed into two reaction wells.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated LAMP assays for quantification of Dehalococcoides spp. in groundwater (Kanitkar et al, 2016). Our studies also examined a field-able means to concentrate bio-mass from groundwater via Sterivex cartridges and direct amplification from filtrate elution on a field-ready Gene-Z device (Stedtfeld et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial genomic studies are currently the most popular molecular identification and classification method of microorganisms in different types of samples based on the selection of one or more specific molecular target(s), such as DNA, RNA and protein, without the requirement to grow in their culture media [ 107 ]. Genetic microbial detection assays can be classified into genome GC% (Guanine + Cytosine) contents, pattern amplification (polymerase chain reaction; PCR, and loop mediated isothermal amplification; LAMP), DNA/RNA hybridization, genome polymorphism (such as RFLP: restriction fragment length polymorphism and AFLP: amplified fragment length polymorphisms) and gene sequencing [ 108 , 109 , 110 ]. In addition to the sample preparation and genome extraction, the majority of these methods need a nucleic acid amplification and an amplicon analysis step [ 110 ].…”
Section: Genomic Based Analysismentioning
confidence: 99%
“…The sample preparation and DNA extraction steps are very challenging steps due to the removal of inhibitors from genomic samples and accurate measurement of the initial genomic contents per specific amounts of sample, which is used in quantitative methods [ 110 ]. These samples are always passed through an enrichment step, which can be performed by overnight incubation of bacteria in a specific sample (only limited to cultivable bacteria), centrifugation, and immunomagnetic separation [ 108 , 109 , 110 ]. These two latest samples can be applied for the removal of sample matrix from the microorganisms, which indeed is useful for removal of inhibitors from the genome [ 108 , 109 , 110 ].…”
Section: Genomic Based Analysismentioning
confidence: 99%